Could Toxomplasma gondii infection be dangerous? - Systematic review - Frącz, Gabriela; Kuliga, Klaudia; Kuliga, Marcin; Musz, Kinga; Socha, Agnieszka; Śnieżek, Kinga (Journal of Education, Health and Sport, 2023)
Introduction: Toxoplasma gondii is an intracellular protozoan commonly found in humans in the form of three main forms: tachyzoite, tissue cyst and oocyst. The definitive host is the Felidae family, and one of the intermediate hosts is humans. The most common routes of infection are ingestion of raw or undercooked meat, water and food contaminated with oocysts. Among the forms of infection, we distinguish between the acquired form and the much more dangerous congenital form. Aim of the study: The objective of the study was to rewiev the literature describing the dangerous impact of Toxoplasma gondii infection on human. Methods and materials: : We reviewed the literature available in the PubMed database, using the key words: "toxoplasma gondii"; "congenital toxoplasmosis"; "pregnacy". Results: T. gondii infection is particularly dangerous in pregnant women, due to the high risk of vertical transmission of the infection to the developing fetus. The clinical presentation of congenital toxoplasmosis depends on the gestational age at which the infection occurred. Pathognomonic signs of congenital toxoplasmosis include Sabin-Pinkerton Triad, which includes inflammation of the retina and choroid of the eye, dilatation of the brain's ventricular system and intracranial calcifications. Available pharmacotherapy works on tachyzoites present in the initial phase of acquired infection, congenital infection and reactivated infection in immunodeficient patients, available drugs do not work on tissue cysts. Conclusion: The consequences of Toxoplasma gondii infection are particularly dangerous for the fetus, so pregnant women should pay special attention to hand hygiene and thorough washing of the food they eat. For this reason, it is extremely important to educate pregnant women about health issues and draw attention to the possible consequences of T.gondii infection.